Dynamics of zoosporic parasites in summer phytoplankton communities of the Baltic Sea - Van den Wyngaert; Silke; Nawaz, Ali; Alacid, Elisabet; Wood-Rocca, Steffaney M.; Reñé, Albert; Garcés, Esther; Kremp, Anke; Wurzbacher, Christian (Oxford University Press (OUP), 2026)
Zoosporic parasites significantly influence aquatic ecosystems by infecting various phytoplankton taxa, but their interactions in brackish ecosystems remain largely unexplored. This study explores microbial communities and parasitic interactions with summer phytoplankton communities at six brackish coastal sites in the northern Baltic Sea. We hypothesized that small-scale spatial heterogeneity in environmental conditions would lead to distinct assemblages of microbial communities and phytoplankton-parasite interactions. By combining DNA metabarcoding, single-cell sequencing, and microscopy, we provide the first community-level qualitative and quantitative assessment of zoosporic parasites infecting summer phytoplankton in the Baltic Sea. Microbial communities varied significantly across sites, with salinity as primary driver of eukaryotic diversity. Chytrid fungi were the dominant parasites, infecting green algae, diatoms, and filamentous cyanobacteria, with infection rates up to 5.8% of phytoplankton biomass. Sequences from brackish chytrids clustered with those from freshwater environments, reflecting polyphyletic patterns linked to host taxa. Phytoplankton-parasite interactions were influenced by host abundance and site-specific conditions with correlation analysis suggesting broader host ranges and potential generalist behavior in some chytrid species. Additionally, an unidentified oomycete infected up to 85% of the toxic bloom-forming cyanobacterium Nodularia spp. This study highlights the ecological relevance of zoosporic parasites in the Baltic Sea and emphasizes the need for further research into their role in phytoplankton bloom dynamics.This first community-level assessment of phytoplankton-zoosporic parasite interactions in the Baltic Sea highlights their diversity, abundance, and potential role in regulating harmful algal blooms and shaping phytoplankton communities.